PENGELOLAAN KOLEKSI MUSEUM RUMAH ADAT NAN BAANJUANG DI KAWASAN TAMAN MARGA SATWA DAN BUDAYA KINNANTAN KOTA BUKITTINGGI, SUMATERA BARAT - Willi Wandira; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Museum of Rumah adat Nan Baanjuang is one of the museums located in the City of Bukittinggi. this museum has various types of collection of enography, numismatic and biologika. in the management of the museum there are four indicators namely planning, organizing, directing and supervision. The purpose of this study (1) To Know How Management of Museum Collection at Traditional House Nan Baanjuang in Kawasan Taman Culture and Kinantan Culture Bukittinggi City (2) To Know What Is The Obstacle In The Management Of Museum Of Traditional House Of Nan Baanjuang In Located Wildlife Park And Culture Kinantan City Bukittinggi This research design using qualitative method with descriptive approach, which the researchers will take data from informants who know clearly about the Museum of Traditional Rumah Adat Nan Baanjuang in the Area of Wildlife Park and Culture Kinantan City Bukittinggi.The results showed that in the management of museum collections in Rumaah Adat Nan Baanjuang there are four stages of collection procurement, collection recording, collection storage and collection maintenance. constraints faced in the management of the museum is a lack of funding, lack of trained human resources.Keywords: Museum, Management, Management of museum collections